PERAN GEN STRUKTURAL, GEN NON-STRUKTURAL, DAN UNTRANSLATED REGION DALAM PERAKITAN VIRUS DENGUE - Pangerapan, Meiranty C.; Kolondam, Beivy J. (UNIVERSITAS SAM RATULANGI, 2015)
Abstract: Dengue virus is a single-stranded RNA virus that belongs to Flaviviridae family. This virus causes dengue fever which is transmitted by Aedes aegypti dan Aedes albopictus. There are four serotypes of dengue virus; all of them can cause dengue fever. Understanding the genomics of dengue virus is important for research and diagnostics. The genome of dengue virus is 11 kilo-base long. It consists of 5’-untranslated region (5’-UTR), three structural genes (coding capsid protein, pre-membrane/membrane, and envelope), seven non-structural genes (coding NS1, NS2A, NS2B, NS3, NS4A, NS4B, and NS5 proteins) and 3’-UTR. Non-structural genes are encoding proteins of viral RNA replication, interferon response, viral assembly and secretion, endoplasmic reticulum membrane invagination induction, immune-mediator induction, and RNA 5’-caping.Keywords: dengue virus, genome, structural genes, non-structural genes, untranslated region.Abstrak: Virus dengue merupakan virus RNA beruntai tunggal yang termasuk dalam famili Flaviviridae. Virus ini adalah penyebab penyakit demam berdarah dengue yang ditransmisikan melalui nyamuk Aedes aegypti dan Aedes albopictus. Ada empat serotipe virus dengue yang telah dikenal secara luas yang ada semuanya dapat menimbulkan penyakit demam berdarah. Pemahaman tentang genomik virus dengue sangat penting untuk pengembangan penelitian dan juga untuk keperluan diagnostik. Genom virus dengue memiliki panjang 11 kilo basa. Genomnya tersusun atas 5’-untranslated region (5’-UTR), tiga gen struktural (mengodekan protein kapsid, premembran/membran dan amplop), tujuh gen non-struktural (mengodekan protein NS1, NS2A, NS2B, NS3, NS4A, NS4B dan NS5) dan 3’-UTR. Gen-gen non-struktural mengodekan protein untuk replikasi RNA virus, respon interferon, perakitan, sekresi partikel virus, menginduksi invaginasi membran retikulum endoplasma, induksi imunomediator dan penambahan tudung pada ujung 5’ RNA.Kata kunci: virus dengue, genom, gen struktural, gen non-struktural, untranslated region